Production functions of irrigated coffee under different planting densities - Serra, Edilson Lopes; Scalco, Myriane Stella; Guimarães, Rubens José; Colombo, Alberto; Morais, Augusto Ramalho de; Carvalho, Carlos Henrique Mesquita de (Coffee Science - ISSN 1984-3909, 2013)
The aim of this study was to evaluate criteria for irrigation and planting densities best suited to coffee growing to maximize yield. The experiment was conducted in an area of the Department of Agriculture, Federal University of Lavras, Minas Gerais, Brazil, in a randomized complete block design with split-plots and four replications. Planting was carried out using healthy coffee seedlings of the Ruby MG-1192 cultivar. It was observed that the use of irrigation provided for significant increases in processed coffee yield in high density planting from 10,000 to 20,000 plants ha-1. Irrigations based on tensions from 60 kPa to 100 kPa are sufficient to meet the water requirements of coffee in dense plantings, but the increase in the number of plants from 10,000 to 20,000 compromises the sustainability of the crop through the disproportionate increase in water consumption for irrigation, with small increases in yield. For the irrigation tension of 60 kPa, the relative increase in yield outweighs the other criteria for irrigation, with 13,750 plants ha-1 being the number of plants indicated.